Computational Characterization of the Binding Properties of the HIV1-Neutralizing Antibody PG16 and Design of PG16-Derived CDRH3 Peptides - Deubler, Manuel; Weißenborn, Lucas; Leukel, Simon; Horn, Anselm; Eichler, Jutta; Sticht, Heinrich (Biology, 2023)
PG16 is a broadly neutralizing antibody that binds to the gp120 subunit of the HIV-1 Env protein. The major interaction site is formed by the unusually long complementarity determining region (CDR) H3. The CDRH3 residue Tyr100H is known to represent a tyrosine sulfation site; however, this modification is not present in the experimental complex structure of PG16 with full-length HIV-1 Env. To investigate the role of sulfation for this complex, we modeled the sulfation of Tyr100H and compared the dynamics and energetics of the modified and unmodified complex by molecular dynamics simulations at the atomic level. Our results show that sulfation does not affect the overall conformation of CDRH3, but still enhances gp120 interactions both at the site of modification and for the neighboring residues. This stabilization affects not only protein–protein contacts, but also the interactions between PG16 and the gp120 glycan shield. Furthermore, we also investigated whether PG16-CDRH3 is a suitable template for the development of peptide mimetics. For a peptide spanning residues 93-105 of PG16, we obtained an experimental EC50 value of 3 (Formula presented.) (Formula presented.) for the binding of gp120 to the peptide. This affinity can be enhanced by almost one order of magnitude by artificial disulfide bonding between residues 99 and 100F. In contrast, any truncation results in significantly lower affinity, suggesting that the entire peptide segment is involved in gp120 recognition. Given their high affinity, it should be possible to further optimize the PG16-derived peptides as potential inhibitors of HIV invasion.
CRIS-Team Scopus Importer:2023-07-28
Keywords: antibody; antibody mimetic peptides; HIV-1; molecular dynamics; peptides; PG16

Smaller, Stronger, More Stable: Peptide Variants of a SARS-CoV-2 Neutralizing Miniprotein - Weißenborn, Lucas; Richel, Elie; Hueseman, Helena; Welzer, Julia; Beck, Silvan; Schäfer, Simon; Sticht, Heinrich; Überla, Klaus; Eichler, Jutta (International Journal of Molecular Sciences, 2022)
Based on the structure of a de novo designed miniprotein (LCB1) in complex with the receptor binding domain (RBD) of the SARS-CoV-2 spike protein, we have generated and characterized truncated peptide variants of LCB1, which present only two of the three LCB1 helices, and which fully retained the virus neutralizing potency against different SARS-CoV-2 variants of concern (VOC). This antiviral activity was even 10-fold stronger for a cyclic variant of the two-helix peptides, as compared to the full-length peptide. Furthermore, the proteolytic stability of the cyclic peptide was substantially improved, rendering it a better potential candidate for SARS-CoV-2 therapy. In a more mechanistic approach, the peptides also served as tools to dissect the role of individual mutations in the RBD for the susceptibility of the resulting virus variants to neutralization by the peptides. As the peptides reported here were generated through chemical synthesis, rather than recombinant protein expression, they are amenable to further chemical modification, including the incorporation of a wide range of non-proteinogenic amino acids, with the aim to further stabilize the peptides against proteolytic degradation, as well as to improve the strength, as well the breadth, of their virus neutralizing capacity.
CRIS-Team WoS Importer:2022-06-24
Keywords: SARS-CoV-2; virus; peptides; structure-based design; synthetic peptides; peptide mimics